PERBEDAAN POLA ASUH TERHADAP PERTUMBUHAN ANAK USIA 1-3 TAHUN PADA IBU BEKERJA DAN TIDAK BEKERJA - Qomar, Umi Laelatul; Sofiana, Juni; Na'mah, Lutfia Uli (Jurnal Ilmiah Kesehatan Keperawatan, 2016)
The children growth is an increased structure and function of the body which become more complex. Taking care model in this case is an act feeding practices about employed mother and unemployed mother attitudes in choosing foods, preeparing meals, feeding can be met, so the growth of children can growth well.The aim of this study is to know the difference of taking care model with growth on children 1-3 years old between employed mother and unemployed mother in the Adimulyo Village Adimulyo District Kebumen region.This research used the analitical survey with cross sectional approach. The difference test used the t-test independent sample test where the sampling used total sampling. The taking care model’s data is got by using questionnaire, while the children growth using Antropometric Calculator according standar of WHO NCHS.Based on research showed that there is a difference between taking care model with children growth on 1-3 years old in employed mother and unemployed mother in the Adimulyo Village Adimulyo District Kebumen Region total respondents is 60 contain employed mother and unemployed motherthe result t-score = -2,227 with sig (2-tailed) 0,03, while the difference between taking care model employed mother and unemployed is got score of t = -6034 with sig (2-tailed) 0.00.The children growth on employed mothers is better than unemployed mother have an income that can be used to improve their children nutrition, assisten by others in rissing children, while than the level of knowledge and education employed mother to know good parenting. Keywords: Taking Care Model, Growth, Children